Analisis Strategi Promosi Dalam Meningkatkan Penggunaan Jasa Bimbingan Belajar Pada Yayasan Bintang Nusantara Cakra Bekasi - Nina Imani; Baby Poernomo (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The promotion strategy is one way to win a sustainable competitive advantage for company that produces goods or services. One of the companies engaged in services is Bintang Nusantara Cakra tutoring. The type of research used in this research is qualitative with a case study method. The data collection technique uses 6 indicators of Fandy Tjiptono's theory promotion mix in Dellamita, M.F (2014). The data collection technique used semi-structured interview methods and participant observation. The data collection is supported by documentation in the form of photographs with resource persons and internal company data. Test the validity of the data in this study using triangulation data collection techniques. The results showed that Yayasan Bintang Nusantara Cakra Bekasi needs corrective and improvement of promotion strategies on 6 promotion mix factors by implementing contemporary promotion strategy through the application of role models, determining appropriate target objects, and maximizing the use of social media by utilizing paid promotion or endorsement features to appropriate figures and the use of billboards and pennants around the building environment to help enlarge the scope of advertising and achieve an increase in the number of costumers.